Trinidad and Tobago: a country paper (ILO. PREALC Port of SpainTT, 1991)
Identifies programmes which have been proposed and implemented by the government. Considers the special programmes in training and development of young people and entrepreneurs which have been put in place to facilitate the necessary changes. These emphasize access to credit; market opportunities and facilities and the availability of appropriate technology. Sees the present programme as directionally sound but requiring further collaboration between the Government, private sector, Trade Union Movement, the public and international lending and support institutions.
DC